The Influence Of Total Quality Management And Raw Material Quality On Cost Efficiency In Coffee Shops In Makassar City - Utari Nur Umrah; Suryanti, Suryanti; Hafid, Normadia; Utama, Riyanda Putra (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Cost efficiency aims to improve profitability by reducing unnecessary costs, such as rework costs or losses due to defective products, while ensuring that products or services remain of high quality. This study aims to examine the influence of the implementation of total quality management and raw material quality on cost efficiency in coffee shops in Makassar City. The data in this study were obtained from coffee shops located in Makassar City that agreed to participate as respondents. This research uses primary data by conducting field research, distributing questionnaires/statements to 90 respondents. The data analysis method employs a specialized multiple linear regression analysis application with a quantitative approach. The results of this study indicate that: (1) The hypothesis test results show that the variable of total quality management implementation has a positive and significant effect on improving cost efficiency in coffee shops in Makassar City. (2) The hypothesis test results show that the variable of raw material quality has a positive and significant effect on cost efficiency in coffee shops in Makassar City.